How migratory shorebirds selectively exploit prey at a staging site dominated by a single prey species. (9th November 2016) - Choi, Chi-Yeung; Battley, Phil F.; Potter, Murray A.; Ma, Zhijun; Melville, David S.; Sukkaewmanee, Parinya
Abstract: Competition intensity depends on the number of competitors and the amount of resources available. Coexistence of potential competitors can be enabled through niche differentiation or high resource availability. Using diet analysis, we investigated which of these 2 mechanisms was in play for coexisting shorebirds at a major staging site in the northern Yellow Sea, China, during northward migration in 2011 and 2012. Competition for food at this site is expected to be intense, with an estimated 250, 000 migratory shorebirds gathering annually to refuel over a short period. Great Knots ( Calidris tenuirostris ), Eurasian Oystercatchers ( Haematopus ostralegus osculans ), and Red Knots ( C. canutus ) selected mostly the bivalve Potamocorbula laevis, whereas Bar-tailed Godwits ( Limosa lapponica ) had a broader diet and showed selection for polychaetes, even though most of their biomass intake was of P. laevis . Although all of these shorebirds fed on P. laevis, they showed different size selection and used different feeding methods. Bar-tailed Godwits, Great Knots, and Red Knots mainly swallowed P. laevis whole and preferred medium-sized P. laevis with relatively high ratios of flesh content to shell mass. By contrast, Eurasian Oystercatchers stabbed open P. laevis, ingested only the flesh, and preferred large P. laevis that provided the highest energetic return per prey taken. Despite evidence of niche differentiation in prey selection, the diets between the numerically dominant Bar-tailed Godwits and Great Knots overlapped substantially. Their coexistence seems to be enabled by high resource availability rather than niche separation.